(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2006)
The data about locations and ecology for 25 new for Crimean peninsula species of lichens: Acarospora umbilicata Bagl., Arthonia pruinata (Pers.) A.L. Sm., Aspicilia maculata (H. Magn.) Oxn., Bacidia subincomta (Nyl.) Arnold, Bryoria bicolor (Ehrh.) Brodo & Hawksw., Caloplaca ammiospila (Wahlenb.) H. Oliv., Catinaria atropurpurea (Schaer.) Vĕzda & Poelt, Collema limosum (Ach.) Ach., Endocarpon pusillum Hedwig, Hymenelia ceracea (Arnold) M. Choisy, Lecidella flavosorediata (Vĕzda) Hertel & Leuckert, L. scabra (Taylor) Hertel & Leuckert, Leptogium cyanescens (Rabenh.) Körb., L. intermedium (Arnold) Arnold, Micarea bauchiana (Körb.) V. Wirt & Vĕzda, Ochrolechia szatalensis Vers., Opegrapha rupestris Pers., Oxneria falax (Hepp.) S. Kondr. & Kärnef., Phaeophyscia ciliata (Hoffm.) Moberg, Phaeophyscia sciastra (Ach.) Moberg, Ramalina dilacerata (Hoffm.) Hoffm., Strigula stigmatella (Ach.) R.C. Harris, Trapelia obtegens (Th.Fr.) Hertel, Thelidium zwackii (Hepp.) A. Massal., Thrombium epigeum (Pers.) Wallr. are provided.